Analysis Of Customer Decisions In Choosing BSI Easy Wadiah And BSI Easy Mudharabah Savings Products - Wati; Okta Mellya Rossa; Andika Hariyanto Surbakti (P3M - STAI Kuningan, 2024)
In choosing a savings product, customers make decisions based on their individual needs and preferences, considering the advantages and disadvantages of each product. Bank Syariah Indonesia offers two savings products that customers can choose from: Easy Wadiah Savings and Easy Mudharabah Savings. Despite the presence of numerous conventional banks in the area, the local community continues to trust and prefer savings products from Bank Syariah Indonesia due to the convenience offered and their perception of Islamic banks as interest-free financial institutions, which strengthens their confidence in saving money with Bank Syariah Indonesia. The purpose of this study is to analyze customer decisions in selecting BSI Easy Wadiah and BSI Easy Mudharabah savings products at Bank Syariah Indonesia KCP Cirebon Arjawinangun. The research uses a descriptive method with a qualitative approach. Data collection techniques include observation, interviews, and documentation. The findings reveal that the decision-making process follows five stages, where customers select the savings product that best suits their needs and preferences. Customers who choose the Easy Wadiah Savings product are primarily motivated by the absence of administrative fees, while those who opt for the Easy Mudharabah Savings product are attracted by the profit-sharing system. Both choices are driven by the desire for a sharia-compliant savings product, as both offerings are in line with Islamic banking principles. Initial information about the Easy Wadiah and Mudharabah savings products is often obtained from friends or relatives, followed by detailed explanations provided by customer service representatives. Respondents stated that both savings products meet their expectations and align with their financial needs.